INFLUENCE OF A SEA-BREEZE CIRCULATION TO FLUX EXCHANGE AND TURBULENCE IN JAKARTA - DZAKIRA SAHLA (12813027) , HAURA
An observations on Influence of a sea-breeze circulation (SBC) to flux exchange and turbulence in Jakarta has been conducted with Himawari-8 Satellite image band VIS B03 (0,86 Ã‚Âµm) and stationary micrometeorological observation. The movement of cumuliform cloud over Jakarta which seen from satellite data has drawn into an isochrone graph. It has two main pattern, straight and sloping toward the coastline. The synoptic wind in level 700 mb has been used for investigate it. Straight isochrone pattern is caused by the gradien winds between the SW and SE, while the sloping isochrone pattern is caused by the slightly offshore synoptic gradien - between the W and NW. Surface roughness also play an important role to control the propagation speed of the sea breeze. The sea breeze front (SBF) could reduce the quantity of sensible heat flux when it passing through the site. For both horizontal momentum flux of u'w' and v'w' are discovered to have a reversal of transfer momentum from downward to upward directly when the SBF pass the coastal area. Time of propagation of the SBC could affect the turbulent intensity which measured by Turbulent Kinetic Energy (TKE). If the SBC tend to propagate later in the noon then the air are very turbulent across the site before the SBF came into the site.